Caracterización morfológica en el cultivo de pitahaya (Hylocereus spp) en el Ecuador - Cevallos Macías, Kevin Liwinsgton (2022)
The present document was shown with the purpose of strengthening the knowledge regarding the importance of the morphology of the pitahaya (Hylocereus spp.) crop, often called "dragon fruit", it is a special fruit whose reputation has spread throughout the world. Its popularity is due to its physical-chemical properties, nutrition and bioactive compounds that make it a functional food, widely used for its excellent organoleptic properties and commercial value. In the country, there are two ecotypes of yellow pitahaya, the so-called "Pichincha" or also known as “Nacional” (fruits weighing up to 150 g), which is grown in northwestern Pichincha, and the “Palora” ecotype (fruits weighing up to 350 g), grown in Morona Santiago (Palora) and in Pichincha. The dragon fruit cactus is a perennial epiphytic plant with a succulent green, triangular jointed stem. Its body consists of three wavy wings with jagged edges and horns. Body segments can be up to 6 m long. Each toothed wing tube has 1-3 short spines 1.5 cm thick, some species have more spines than others. Aerial roots grow from the base of the long-lasting stem and give the plant an anchor for climbing a wall, rock or tree. It blooms at night, green outside and white inside, about 30 cm long and 23 cm wide, with lobed green moons. They are bell-shaped and very fragrant, they open late at night and wither at dawn, the characteristic shape of their fruit is ellipsoidal (referential to a berry), with a diameter between 10-12 cm, depending on its size. species.